posted by kristie on .
Could you show me step by step how to find the inverse of this problem:
log with base of 2 (x+1)
It is not clear what the problem is. You are given a function of x. Let's calli it y. Are you trying to come up with an equation for x in terms of y?
If log(base2)of (x+1) = y,
then 2^y = x+1 and
x = 2^y - 1
the exact problem was :
f(x) = log(base2)(x+1)
"find f^(-1)(x)" means find the inverse function of f(x).
I believe that my previously derived fomula for x in terms of y IS the inverse function. Just relabel it as
f^-1 (x) = 2^x -1
f^(-1) of (f(x)) = x
give mats formula
i could answer that but can you tell me what this sign^ stands for please!!!!!